ADSORÇÃO DE CORANTE INDUSTRIAL REATIVO PRETO 5 UTILIZANDO CARVÃO VULCAN XC-72 - Mota, Marcos Vinicius de Carvalho (2020)
Nowadays, problems causedbywater resources contaminationhave been more impactful. The textile industries effluent has a large concentration of dyes and pigments, whose change color, turbidity, dissolved oxygen, among other parameters unbalance the local e